Efeitos neuroprotetores do extrato supercrítico de piper divaricatum em um modelo experimental de isquemia cortical em ratos adultos - SILVA, Amanda Silva da (2023)
Stroke is one of the main causes of disability and death in the world, with ischemic stroke being the most prevalent. Nowadays, the only pharmacological treatment available for ischemic stroke is the recombinant tissue plasminogen activator (rt-PA), a drug that is widely used due to its short therapeutic window and severe side effects. Therefore, studies are necessary for the identification of neuroprotective drugs capable of avoiding secondary injury after acute neural disorders. Piper divaricatum plant is considered in the folk medicine as possessing both anti-inflammatory and anti-oxidant effects, with some scientific evidence available. This plant is also used for treatment of rheumatic diseases. Nevertheless, its potential anti-inflammatory and neuroprotective effects have not yet been investigated using experimental models of brain stroke. In this study, the anti-inflammatory and neuroprotective potential of the supercritical extract of Piper divaricatum (100 mg/kg, i.p) was investigated using an experimental model of cortical ischemia induced by microinjections (80 pmol/µl) of endothelin-1 (ET-1) in adult Wistar rats. Six animals were divided in 2 experimental groups: control group (ET-1 + 5% tween, n = 3) and treated group (ET-1 + supercritical Piper divaricatum extract, n = 3). The brains were processed for histological analysis with cresyl violet staining. After histological analysis, it has been observed tissue pallor, loss of neuronal bodies and inflammatory infiltrate in the ischemic area of both experimental groups. However, in the animals treated with supercritical Piper divaricatum extract, there was a decrease in infarct area and reduction of inflammatory infiltrate. These results suggest that Piper divaricatum extract, at the investigated concentration, decreases the infiltrate of inflammatory cells, mainly mononuclear cells, with concomitant neuroprotective effects after experimental cortical ischemia in adult rats. Future studies, using specific markers of neurons, leukocytes and glial cells, are necessary to confirm the results here described.